Економічна стійкість підприємств в умовах війни - Беліменко, Олександр Ігорович; Belimenko, Oleksandr; Блакита, Ганна Владиславівна; Blakyta, Hanna (Запоріжжя : Видавничий дім «Гельветика», 2025)
UA: У статті проведено аналіз економічної стійкості підприємств в умовах війни. Зокрема, досліджено стан та динаміку змін основних макроекономічних показників, як одного з головних чинників впливу на розвиток підприємництва в країні. Досліджено ділову активність субʼєктів господарювання за період повномасштабного вторгнення російської федерації, у тому числі субʼєктів малого підприємництва – ФОП, як основної складової вітчизняного господарювання. Проаналізовано основні зовнішні та внутрішні фактори, які впливають на стабільність бізнесу в умовах війни. За отриманими результатами аналізу визначено напрями відновлення бізнесу від шокових станів та заходи, впровадження яких дозволить відновити стабільність з метою досягнення належного рівня економічної стійкості. /// EN: The article provides a comprehensive analysis of the economic resilience of enterprises in wartime, taking into account the key challenges and features of business functioning in crisis conditions. In particular, the state and dynamics of changes in key macroeconomic indicators, such as GDP, inflation rate, investment activity, labor market conditions, level of solvency in the domestic market, and tax burden, which are determining factors influencing the development of entrepreneurship in the country, are studied. Particular attention is paid to the analysis of the business activity of business entities during the period of a full-scale invasion of the russian federation, including the functioning of medium, small, micro businesses and individual entrepreneurs (IEOs), which form the basis of the domestic economy. The main challenges enterprises face in wartime are outlined, in particular, logistical difficulties, limited access to financing, changes in consumer trends, challenges in interacting with public authorities and a decrease in the solvency of the population. The article provides a comprehensive analysis of external and internal factors affecting the stability of business activity, including the military-political situation, state support for business, access to international markets, digitalization, and adaptation of enterprises to new conditions for conducting economic activity. Based on the research findings, recommendations have been developed for the restoration of business aftershocks, in particular strategic measures to increase its stability, adaptability and resilience. These recommendations include policy-driven initiatives aimed at fostering financial liquidity, enhancing institutional support for entrepreneurs, promoting diversification of business operations, and facilitating international cooperation to attract foreign investments and aid. Additionally, the study outlines targeted measures to strengthen economic stability in the post-war period, ensuring sustainable development and reinforcing the adaptive capacity of enterprises to future crises.
Economic resilience of enterprises in war conditions
Keywords: економічна стійкість; підприємство; стійкість; стабільність; виклики; economic resilience; enterprise; resilience; stability; challenges